Familiarity Effect of Emotional Stimuli onto EEG Signals - Polat, Hasan; Ozerdem, Mehmet Sirac (IEEE, 2015)
The aim of this study was to investigate the familiarity effect of emotional stimuli onto EEG signal. Familiar and non familiar stimuli were determined according to participants' rating and EEG segments related to familiar and non familiar stimuli were analyzed. Discrete wavelet transform (DWT) was used as filter to get the interested frequency range of EEG signals. Power spectral density (PSD) of filtered EEG signals was obtained by using Welch method. The power spectrum of EEG signals was considered as familiarity effects of emotional stimulus. As a conclusion, it was observed that different states of familiarities related to emotional stimulus cause different values of PSD over EEG signals.
Medical Technologies National Conference (TIPTEKNO) -- OCT 27-29, 2016 -- Antalya, TURKEY
Keywords: EEG; Familiarity; Discrete Wavelet Transform; Power Spectral Density